2023
DOI: 10.1002/jcv2.12153
|View full text |Cite
|
Sign up to set email alerts
|

Examining Children and adolescent mental health trajectories during the COVID‐19 pandemic: Findings from a year of the Co‐SPACE study

Abstract: Background: A major concern throughout the COVID-19 pandemic has been on young people's experiences with mental health. In this study we mapped children and adolescents' mental health trajectories over 13 months of the pandemic and examine whether family, peer, and individual-level factors were associated with trajectory membership. Methods: This study focuses on a sub-sample from the Co-SPACE study of 3322 children and adolescents (aged 4-16 years) for whom parents completed a survey at Time 0 and at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The RCT was conducted during spring 2021 and summer 2021, when pandemic-related restrictions were beginning to ease (ie, children were not homeschooled en masse, and restrictions on social contacts had relaxed). In this sense, we are unable to generalize our findings to more restrictive lockdown periods or to nonrestricted contexts, and parents of children in Co-SPACE reported a drop in conduct problems when restrictions eased [5]. However, during the RCT, there was continued concern and uncertainty about the course of the pandemic and its continued impact.…”
Section: Limitationsmentioning
confidence: 67%
See 3 more Smart Citations
“…The RCT was conducted during spring 2021 and summer 2021, when pandemic-related restrictions were beginning to ease (ie, children were not homeschooled en masse, and restrictions on social contacts had relaxed). In this sense, we are unable to generalize our findings to more restrictive lockdown periods or to nonrestricted contexts, and parents of children in Co-SPACE reported a drop in conduct problems when restrictions eased [5]. However, during the RCT, there was continued concern and uncertainty about the course of the pandemic and its continued impact.…”
Section: Limitationsmentioning
confidence: 67%
“…Children's behavioral and emotional problems increased during the pandemic [2], with individuals with preexisting vulnerabilities at particular risk [3]. COVID-19: Supporting Parents, Adolescents and Children during Epidemics (Co-SPACE), a UK-wide general population study, confirmed this pattern during both the first and second UK lockdowns [4,5]. Findings from Co-SPACE and other studies show that increases in parental stress and child-related help seeking were also reported [6,7].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…These conditions contributed to worsening mental health for children and their parents, which in some cases will have persisted once schools reopened 15. Adverse mental health impacts have been most sustained for children with special educational needs and disabilities, neurodevelopmental disorders, fewer close friendships and those living in families with lower incomes and higher parental stress 16. On the other hand, school closures provided a welcome relief from the stresses of school for some children, including those with pre-existing EBSA.…”
Section: Risk Factors In the Post-pandemic Contextmentioning
confidence: 99%